SOCIOLINGUISTIC PERSPECTIVES ON ENGLISH AS A SECOND LANGUAGE: INSIGHTS FROM GLOBAL CONTEXTS - Hanura, Huda; Widiarti, Tri Rini (Global Synthesis in Education Journal, 2025)
This study examines the perceptions of English as a Foreign Language (EFL) students regarding AI-powered language learning tools for academic writing. Academic writing is crucial for Indonesian EFL students, who often struggle with grammar, vocabulary, organization, and coherence. The rise of AI tools offers a promising solution, providing personalized learning and automated feedback to enhance writing skills. Understanding student perceptions is therefore vital to assess the effectiveness and improve these tools. This research identifies the perceived benefits and drawbacks among students in the English Education Study Program at Ahmad Dahlan University. Employing a qualitative method, the study gathered data through semi-structured interviews with six fourteenth-semester students, and documentation. Using thematic data analysis, focusing on understanding the unique meanings from the participants' perspectives. Findings reveal mostly positive perceptions, with students citing ease of use, improved writing quality, and time efficiency as key benefits. AI tools offer immediate feedback, enabling students to correct errors and refine their language skills independently. However, the study also highlights the critical need for digital literacy to evaluate AI-generated suggestions, as the accuracy of feedback can vary. Concerns included potential technology dependence, AI failures in complex academic contexts, and the need for developers to improve algorithms for contextual relevance. In conclusion, AI-powered tools can significantly enhance academic writing when used thoughtfully, provided they are supported by strong digital literacy and faculty guidance, thereby maintaining human cognitive engagement. This encourages adaptive learning environments and opens avenues for future AI development research